Environmental and technological limitations as an effective tool of land management rational use and protection of lands - Dorosh, Y.; Barvinskyi, А.; Kupriyanchik, I.; Svyrydova, L. (Land Management, Cadastre and Land Monitoring, 2022)
The key role of establishing and observing ecological and technological restrictions in the use of arable land for ensuring rational agricultural land use and preserving the land-resource potential of rural areas is proven. Methodical approaches to determining ecological and technological limitations in the use of agricultural land are analyzed. Fragments of the classifier of types of functional purpose of territories and types of functional purpose of territories and their correlation with types of purposeful purpose of land plots are given.The main characteristics of each level of ecological and technological restrictions related to soil cultivation and sowing of agricultural crops are highlighted. The need to establish ecological and technological restrictions on the use of land at the legislative level by introducing a corresponding addition to Article 111 of the Land Code of Ukraine and the possibility of their practical implementation on the basis of the classifier of types of functional purpose of territories developed by the authors was substantiated.It is emphasized the need to introduce changes and additions to Appendix 6 of the current State Land Cadastre Management Procedure regarding the implementation of ecological and technological restrictions in the use of land, which should be based on a 4-level classification in which certain ecological and technological restrictions are associated with the corresponding type of functional purpose cultivated agricultural areas.Key words: agricultural land, land protection, steepness of slopes, ecological and technological limitations, classifier.
Keywords: agricultural land; land protection; steepness of slopes; ecological and technological limitations; classifier.